2010
DOI: 10.1073/pnas.0912802107
|View full text |Cite
|
Sign up to set email alerts
|

UBE2S drives elongation of K11-linked ubiquitin chains by the Anaphase-Promoting Complex

Abstract: The Anaphase-Promoting Complex (APC) is an E3 ubiquitin ligase that regulates mitosis and G1 by sequentially targeting cell-cycle regulators for ubiquitination and proteasomal degradation. The mechanism of ubiquitin chain formation by APC and the resultant chain topology remains controversial. By using a single-lysine APC substrate to dissect the topology of ubiquitinated substrates, we find that APC-catalyzed ubiquitination has an intrinsic preference for the K11 linkage of ubiquitin that is essential for sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
254
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(264 citation statements)
references
References 32 publications
9
254
0
1
Order By: Relevance
“…This could be because of endogenous Ube2s proteins copurified with its E3 APC Cdc27 complex. 21 A previous study showed that Ube2s mediates K11-linked polyubiquitin chain assembly on substrates. 21 To verify this, we used a Ub-K11R mutant to perform the in vitro ubiquitination assay and found that this mutation significantly reduces the assembly of polyubiquitin chain on Sox2 (Figure 2d), suggesting that Ube2s modifies Sox2 through the formation of K11-linked polyubiquitin chains.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This could be because of endogenous Ube2s proteins copurified with its E3 APC Cdc27 complex. 21 A previous study showed that Ube2s mediates K11-linked polyubiquitin chain assembly on substrates. 21 To verify this, we used a Ub-K11R mutant to perform the in vitro ubiquitination assay and found that this mutation significantly reduces the assembly of polyubiquitin chain on Sox2 (Figure 2d), suggesting that Ube2s modifies Sox2 through the formation of K11-linked polyubiquitin chains.…”
Section: Resultsmentioning
confidence: 99%
“…21 A previous study showed that Ube2s mediates K11-linked polyubiquitin chain assembly on substrates. 21 To verify this, we used a Ub-K11R mutant to perform the in vitro ubiquitination assay and found that this mutation significantly reduces the assembly of polyubiquitin chain on Sox2 (Figure 2d), suggesting that Ube2s modifies Sox2 through the formation of K11-linked polyubiquitin chains. Furthermore, Ube2s-overexpressed mES cells exhibit a robust elevation of polyubiquitinated Sox2 signal, confirming the capability of Ube2s in ubiquitinating Sox2 in vivo (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations